Writing a textbook and a research book - Hashim, Roosfa (2021)
This paper aims to answer some questions about how to write a textbook and a research book. Therefore, this paper will describe the techniques and methods of writing a textbook for university students and how to write a research book. This paper also explains how to write a proposal for a textbook to be sent to a book publisher. The practices, techniques, writing methods used by reputable book publishers have been studied. This has resulted in an appropriate method for use by selected participants attending textbook and research book writing workshops. This workshop was held on 21 February 2021. A total of 30 participants consisting of International Islamic University Malaysia (IIUM) lecturers have used the method recommended to them. Basically a textbook is written to make it easier for students to learn a subject. A good textbook structure contains opener components, various pedagogical tools, and closer components. A research book is written based on the research that has been done. Because a research book is written to be read by scholars and experts, its structure is more similar to the structure of a thesis or dissertation. Acceptance of participants was obtained through question and answer sessions in this workshop. In conclusion, the techniques and methods of writing textbooks and research books that are proposed have helped to improve the understanding of the authors.